Audiological and clinical outcomes of a transcutaneous bone conduction hearing implant: Six‐month results from a multicentre study. (18th November 2018) - den Besten, Christine A.; Monksfield, Peter; Bosman, Arjan; Skarzynski, Piotr H.; Green, Kevin; Runge, Christina; Wigren, Stina; Blechert, Johan I.; Flynn, Mark C.; Mylanus, Emmanuel A. M.; Hol, Myrthe K. S.
Abstract : Objectives: To compare the hearing performance of patients with conductive and mild mixed hearing loss and single‐sided sensorineural deafness provided with a new transcutaneous bone conduction hearing implant (the Baha Attract System) with unaided hearing as well as aided with a sound processor on a softband. Furthermore, to evaluate safety and subjective benefit before and after implantation of the test device. Participants: Fifty‐four adult patients in five participating centres were enrolled in this prospective study. Baseline data were collected during a pre‐operative visit, and after a softband trial, all patients were implanted unilaterally. Follow‐up visits were scheduled at 10 days, 4, 6, 12 weeks and 6 months. Main outcome measures. Free‐field hearing thresholds pure‐tone average (PTA4 in dB HL; mean threshold at 500, 1000, 2000, 4000 Hz; primary outcome measure). Individual free‐field hearing thresholds, speech recognition in quiet and in noise, soft tissue status during follow‐up and subjective benefit as measured with the Abbreviated Profile of Hearing Aid Benefit (APHAB), Speech, Spatial and Qualities of Hearing Scale (SSQ) and Health Utilities Index (HUI) questionnaires. Results: Implantation of the Baha Attract System resulted in favourable audiological outcomes compared to unaided conditions. On the primary outcome parameter, a statistically significant improvement was observed compared to unaided hearing for the patients with conductive/mixed hearing loss (mean PTA4 difference −20.8 dB HL, SD 9.8; P < 0.0001 ) and for the patients with single‐sided sensorineural deafness (SSD) (mean PTA4 difference −21.6 dB HL, SD 12.2; P < 0.0001 ) . During all audiology tests, the non‐test ear was blocked. Statistically significant improvements were also recorded in speech tests in quiet and noise compared to unaided hearing for the conductive/mixed hearing loss group and for speech in quiet in the SSD group. Compared to the pre‐operative measurement with softband, no significant differences were recorded in the PTA4 free‐field hearing threshold or the other audiological outcomes in either of the groups ( P > 0.05). Soft tissue‐related issues observed during follow‐up included numbness, pain/discomfort at the implant site and to a lesser extent pressure‐related skin complications. A declining trend was noted in the rate of these complications during follow‐up. Approximately 20% of patients reported some degree of numbness and 38% (slight) pain/discomfort at final follow‐up of 6 months. Good results on the subjective benefit questionnaires were observed, with statistically significant improvements on APHAB and SSQ questionnaires, and on the hearing attribute of HUI3. Conclusions: The Baha Attract System provided a significant improvement in hearing performance and subjective benefit compared to the pre‐operative unaided condition (with the non‐test ear blocked). Hearing performance of the Baha Attract was similar to a test situation with the same sound processor on a softband. A proportion of the patients reported numbness and pain/discomfort at the implant site during follow‐up, especially during the first post‐operative weeks. Based on the results of the current multicentre study, the Baha Attract can be considered as a treatment option for patients with the aforementioned hearing losses. Especially in the SSD patients, a careful selection procedure is warranted. Therefore, a pre‐operative trial should be part of the decision‐making process before fitting a patient with the Baha Attract System.